Propriedades de medida do instrumento Patient Specific Functional Scale na asma - Franco, Stephany Costa (2024)
Background: Asthma is a chronic inflammatory lung disease with persistent symptoms and/or high frequency of exacerbations, which might result in important disability. The Patient Specific Functional Scale (PSFS) is an instrument that assesses activity limitations. To date, there are no studies that have evaluated the measurement properties of the PSFS in asthma. Objective: To analyze the measurement properties of the PSFS in individuals with asthma. Methods: This is a methodological study that included adults with asthma followed up at a pulmonology outpatient clinic. The measurement properties evaluated were: reliability, construct and content validity; besides ceiling and floor effects, and acceptability and feasibility. Convergent and divergent validity were assessed by correlating the PSFS score with the Asthma Quality of Life Questionnaire (AQLQ) score and lung function, respectively. The PSFS score was compared between groups according to asthma control to determine known-group validity. Content validity was assessed by linking the activities reported by participants in the PSFS with the activity and participation domains of the International Classification of Functioning, Disability and Health (ICF). Floor and ceiling effects were assessed according to the percentage of individuals found at the extremes of the scale scores. Results: 100 individuals were included, 88% women, with a mean age of 56±14 years. The mean PSFS score was 4.1±2.3 points. Regarding reliability, the intraclass correlation coefficient was 0.95 (95% confidence interval (CI) 0.88 to 0.97, p<0.0001). A weak correlation was observed between the PSFS and the total AQLQ score (r=0.27, p=0.006) and a moderate with the AQLQ activity limitation domain (r=0.34, p=0.001). A weak correlation was observed with the forced expiratory volume in 1 second (r=0.16, p=0.19). Participants with controlled and uncontrolled asthma had a mean of 4.7 ± 2.6 and 3.6 ± 1.8 points, respectively (p=0.03). 97% of the items reported by the participants were classified in the activity and participation domain of the ICF. No ceiling or floor effects were observed. 83% of the sample reported having no difficulty understanding the instrument. Conclusions: The PSFS presents adequate test-retest reliability, construct and content validity, and absence of ceiling and floor effects. In addition, it was easy to understand, proving to be a promising instrument for assessing activity limitations in individuals with asthma.